e-Transformation: Enabling New Development Strategies - Hanna, Nagy K. (Springer New York, 2010)
Could information and communication technology (ICT) become the transformative tool for a new style of global development? Could ICT promote knowledge-based, innovation-driven, and smart, adaptive, participatory development? As countries seek a way out of the present period of economic contraction, they are trying to weave ICT into their development strategies, in the same way organizations have learned to use ICT to transform their business models and strategies. This integration offers a new path to development that is responsive to the challenges of our times. In e-Transformation, Nagy Hanna identifies the key ingredients for the strategic integration of ICT into national development, with examples from around the world.
Keywords: Development Economics; Public Economics; Economic Growth; Development economics; Public finance; Economic growth